Clinical course of patients with hepatocellular carcinoma who experienced radiologic complete response after radioembolization - Moon, Sungmo; Kim, Gyoung Min; Won, Jong Yun; Kwon, Joon Ho; Park, Juil; Han, Kichang; Kim, Man-Deuk; Kim, Hyung Cheol; Kim, Dong Kyu; Choi, Jin Young (Frontiers in Oncology, 2024)
The purpose of this study is to elucidate the patterns of recurrence of hepatocellular carcinoma and to analyze factors that can predict recurrence after complete response to radioembolization.A total of 289 consecutive patients who underwent radioembolization for the treatment of hepatocellular carcinoma at a single tertiary center were retrospectively reviewed. Baseline characteristics were collected and compared between the group showing complete response and the group showing noncomplete response. Data on recurrence status, time to recurrence, and the patterns of recurrence among the patients who showed radiologic complete response were collected. The group that maintained complete response and the group that experienced recurrence were compared, and the risk factors affecting recurrence were evaluated by logistic regression analysis.The complete response rate was 24.9% (73/289). Age, sex, tumor markers, maximum tumor diameter, multiplicity, presence of vascular invasion, and target radiation dose were significantly different between the complete response and noncomplete response groups. The recurrence rate after complete response was 38.4% (28/73), and 67.9% (19/28) of recurrences occurred by 8 months after complete response. Eight patients who underwent resection/transplantation after complete response experienced no recurrence. Multiple tumors and a lower target radiation dose were independent risk factors of recurrence after complete response in the multivariate logistic regression.Hepatocellular carcinoma recurrence following complete response after radioembolization is not uncommon and frequently occurs within 1 year after complete response. Multiple tumors and a lower target radiation dose may be risk factors for recurrence.